Tinjauan Yuridis Tindak Pidana Penipuan Social Engineering pada Nasabah Perbankan melalui Aplikasi Chat Whatsapp - Nur Hidayah; Amran (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2023)
The aims of this research are: 1) to find out the practice of social engineering fraud on banking customers via the WhatsApp chat application and 2) to find out the legal sanctions against perpetrators of criminal acts of "social engineering" fraud on the WhatsApp messaging application. This research is a normative-juridical research, namely by examining the legal regulations related to targets related to analysis and construction which are carried out methodologically, systematically and consistently. The data that has been collected and processed will be discussed using a qualitative normative method, namely a discussion that is carried out by interpreting and describing the data that has been obtained and processed, based on legal norms and doctrine. The conclusions of this research are as follows: 1) The soceng or social engeneering mode that is usually carried out by fraudsters via the WhatsApp messaging application is: 1. Making Fake Calls (Fake Caller) 2. Digital Wedding Invitations 3. Sending packages 4. Changes in administration rates for savings fees and finally 5. Ticket notification via What'Sapp chat. 2) The threat of sanctions imposed by soceng fraudsters is regulated in Law no. 3 of 2011 concerning Fund Transfers in articles 81 and 82. Meanwhile, in Law 11 of 2008 concerning Information and electronic transactions, article 32 paragraph 2 with criminal threats in article 48 paragraph 2 and finally the Criminal Code in article 362. The suggestion in this research is that users of messaging applications of any kind, whether from social media or messaging such as WhatsApp, to always be careful and increase vigilance regarding all information provided to other parties. For this reason, increasing literacy, especially banking literacy, is needed to prevent cases of soceng fraud.